2021
DOI: 10.1002/hed.26702
|View full text |Cite
|
Sign up to set email alerts
|

Surgical, clinical, and functional outcomes of transoral robotic surgery used in sleep surgery for obstructive sleep apnea syndrome: A systematic review and meta‐analysis

Abstract: We investigated safety and efficacy of transoral robotic surgery (TORS) for base of tongue (BOT) reduction in obstructive sleep apnea syndrome (OSAS) patients. PubMed, Cochrane Library, and Scopus were searched. A meta‐analysis was performed. Random effects models were used. Thirty‐one cohorts met our criteria (1693 patients). The analysis was based mostly on retrospective studies. The summary estimate of the reduction of Apnea–Hypoxia Index (AHI) was 24.25 abnormal events per hour (95% CI: 21.69–26.81) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
(295 reference statements)
0
10
0
1
Order By: Relevance
“…The incidences of OSA syndrome have increased threefold in the last 20 years [ 29 ]. Single-level surgery had a limited number of successful surgical results in the last two decades [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidences of OSA syndrome have increased threefold in the last 20 years [ 29 ]. Single-level surgery had a limited number of successful surgical results in the last two decades [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of OSA syndrome have increased threefold in the last 20 years [ 29 ]. Single-level surgery had a limited number of successful surgical results in the last two decades [ 29 ]. UPPP with or without tonsillectomy could not only improve the respiratory events during night sleep but also improve sleep quality, depression, sexual function, ventricular function, and promote safe driving in OSA patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on 31 of these studies (1,693 patients) found a 24.3 decline in the AHI (95% CI: 21.69-26.81), a 7.92 decline in ESS (95% CI: 6.50-9.34), a 6.04% increase in the lowest oxygen saturation (95% CI: 3.05-9.03), and 69% in a surgery success rate (95% CI: 64-79). However, these findings provide low evidence for proving the effectiveness of the robot surgeries, because most of the robot surgeries were performed along with soft palate surgeries and the studies did not include any control group [50].…”
Section: Surgical Treatments Of Osamentioning
confidence: 91%
“…Eine aktuelle Meta-Analyse von 31 Studien zeigt ein erfolgsversprechendes Therapieansprechen nach o.g. Kriterien von 69 % nach TORS bei ausgewählten OSAS-Patienten [198]. Während nach TORS-Eingriffen bei OSAS-Patienten keine schwerwiegenden Komplikationen bekannt sind, ist zu beachten, dass die Eingriffe am Zungengrund zu Einschränkungen des Schluckvermögens führen können.…”
Section: Obstruktives Schlafapnoe-syndromunclassified